Enhancement Punching Shear in Flat Slab Using Mortar Infiltrated Fiber Concrete - Shwalia, Ali Sabah Imran; Al-Salim, Nabeel Hasan Ali; Al-Baghdadi, Haider M. (Civil Engineering Journal, 2020)
In this paper, improving the punching shear of slab column connection using mortar infiltrated fiber concrete is studied. Eight specimens of reinforced concrete slabs identical in dimension and reinforcement were tested, six of them were casting with hybrid concrete (normal strength concrete and mortar infiltrated fiber concrete) and two specimens were cast with normal strength concrete as control specimens. All specimens were tested under vertical loading. The mortar infiltrated fiber concrete was cast monolithically with the normal strength concrete at different thickness at one and a half times of the effective depth (1.5d) at the center of the slab, once at all the thickness of cross section of the slab and the others at half thickness either tension or compression face of the slabs all cases cast with two types of fiber. The vertical load was applied upward through a square column with a dimension of (100 mm). In all slabs, no failure in mortar infiltrated fiber concrete was observed. The test results showed that the use of mortar infiltrated fiber concrete improves the punching shear strength for some cases according to the type of fibers and the location of casting mortar infiltrated fiber concrete in slabs. The enhancement in punching shear strength due to using mortar infiltrated fiber concrete at 1.5d square shape (265 mm) ranged from 4% to 46% compared with the control specimens.